Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1093/europace/eun023
|View full text |Cite
|
Sign up to set email alerts
|

Biventricular pacing preserves left ventricular performance in patients with high-grade atrio-ventricular block: a randomized comparison with DDD(R) pacing in 50 consecutive patients

Abstract: BiV pacing minimizes LV dyssynchrony, preserves LV function, and reduces NT-proBNP in contrast to DDD(R) pacing in patients with high-grade AV block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 33 publications
1
32
0
2
Order By: Relevance
“…Information from 9 trials comparing RV and biventricular pacing including a total of 1595 patients is shown in Table. 7-16 Four studies 7-10 (n=534) enrolled patients with AF after AVn ablation, and 5 studies [11][12][13][14][15][16] (n=1061) were conducted in patients with AVB.…”
Section: Randomized Clinical Trials Comparing Rv and Biventricular Pamentioning
confidence: 99%
See 1 more Smart Citation
“…Information from 9 trials comparing RV and biventricular pacing including a total of 1595 patients is shown in Table. 7-16 Four studies 7-10 (n=534) enrolled patients with AF after AVn ablation, and 5 studies [11][12][13][14][15][16] (n=1061) were conducted in patients with AVB.…”
Section: Randomized Clinical Trials Comparing Rv and Biventricular Pamentioning
confidence: 99%
“…In this article, we review the physiological effects of RV pacing, data from observational studies ( Table I in the Data Supplement), [1][2][3][4][5][6] and available randomized trials comparing biventricular versus RV pacing (Table). [7][8][9][10][11][12][13][14][15][16] …”
mentioning
confidence: 99%
“…These studies have tested "de novo" CRT implantation in patients with a conventional pacing indication, both with preserved left ventricular systolic function [67][68][69] and with moderate-severe left ventricular dysfunction [70][71][72]. The results suggest that CRT plays a preventive role with regard to HF mortality/hospitalizations only in patients with left ventricular dysfunction (LVEF <40%).…”
Section: Patient Selectionmentioning
confidence: 99%
“…Pequeños estudios aleatorizados han señalado que los pacientes con disfunción del VI moderada-grave podrían beneficiarse de la TRC en lugar de la estimulación apical del VD convencional (tabla 15) [123][124][125][126][127][128][129][130] . En general, los objetivos primarios de estos estudios se sustituyeron por objetivos hemodinámicos.…”
Section: Estimulación Cardiaca Con Terapia De Resincronización Cardiaunclassified